1988
DOI: 10.1002/jcp.1041370308
|View full text |Cite
|
Sign up to set email alerts
|

Ca‐dependent slow action potentials in human skeletal muscle

Abstract: Slow Ca-action potentials (CaAP) were studied in normal human skeletal muscle fibers obtained during surgery (fibers with both ends cut). Control studies also were carried out with intact as well as cut rat skeletal muscle fibers. Experiments were performed in hypertonic Cl-free saline with 10 or 84 mM Ca and K-channel blockers; muscles were preincubated in a saline containing Cs and tetraethylammonium. A current-clamp technique with two intracellular microelectrodes was used. In human muscle, 14.5% of the fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

1990
1990
1991
1991

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…As previously reported (Nicola Siri et al, 1988) these responses can be elicited in spite of the cut end condition of the fibers. Muscle fibers can also produce abortive non-regenerative Ca responses, or no Ca responses at all.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…As previously reported (Nicola Siri et al, 1988) these responses can be elicited in spite of the cut end condition of the fibers. Muscle fibers can also produce abortive non-regenerative Ca responses, or no Ca responses at all.…”
Section: Discussionsupporting
confidence: 60%
“…It was observed that Ca responses in normal muscle are much more frequent in rat than in human muscles (Nicola Siri et al, 1988). The differences between our findings and those in dystrophic mouse are probably due to differences between species and between animal and human diseases.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations